Building plan approval process / Muhammad Afiq Che Roha - Che Roha, Muhammad Afiq (Universiti Teknologi MARA, Perak, 2014)
This report briefly explain about process of building plan approval. Objective of this report to study the process involve in building plan approval and to identify the problem occur during the building plan approval. Method of study is divided into two methods which are observation and interview method. In observation of study method, this process carried out in working hours. This process begins when the applicant submit the plan at One-Stop (OSC) counter and next processes will be conducted until approval issued by Pasir Mas District Council. In addition, for the interviews conducted during writer methods do practical training. This method can provide a lot of accurate information by interviewing the Mr. Azmi, Mr Kamarul. They were given are goods information to me. Through this method, it is a bit of give and help to the writer to gather information about the research topic of the process approve plan by the Pasir Mas Local Authority method. The finding from this report is the of process of building plan approval is start from applicant send apply to Pasir Mas District Council of One-Stop Centre (OSC) unit, revised application by One-Stop Centre (OSC) unit, checking by technical department, One-Stop Centre (OSC) committee meeting and building plan approval letter give to applicant. Hope with this report can give a lot of advantage and benefit to the render on how to process of building plan approval and the problem occurred.